The violent power struggle in Syria: Scenarios and policy options for the international community - Heiko Wimmen; Muriel Asseburg (Stiftung Wissenschaft und Politik (SWP), 2012)
The violence in Syria continues to escalate. Propaganda-serving reforms devoid of substance and credibility, like the constitutional amendments of February 2012, have done nothing to de-escalate the situation. A return to the status quo ante appears just as implausible as a negotiated settlement. There is now an acute danger of full-blown civil war with the fighting between regime and insurgents spilling over into sectarian bloodshed. Although pressure is growing for the international community to intervene militarily, the foremost goal must be to avoid an uncontrolled escalation of violence and to press for humanitarian organisations to be granted access
Keywords: 320